Zenodo in the Spotlight of Traditional and New Metrics - Peters, Isabella; Kraker, Peter; Lex, Elisabeth; Gumpenberger, Christian; Gorraiz, Juan Ignacio (Frontiers in Research Metrics and Analytics, 2017)
In this case study, we aim to explore the characteristics and the reception of files uploaded to Zenodo and the role the repository plays itself in generating usage. To this end, we first apply descriptive statistics on Zenodo’s full set of data record metadata with DOIs until and including January 2017 (n=141,777 records). Second, we estimate the coverage of Zenodo datasets in the Data Citation Index (DCI) as well as of Zenodo journal articles in the Science Citation Index (SCI), Social Science Citation Index (SSCI) and Arts and Humanities Citation Index (A&HCI), Zenodo books and book chapters in the Book Citation Index, and Zenodo conference papers in the Proceedings Citation Index, and analyse their citedness according to the different data record types in Zenodo (e.g., journal article, dataset, book, or conference paper). Third, we provide a bibliometric analysis of Zenodo records by using different metrics for citedness, including citation, usage and altmetrics. Altmetrics data are gathered from two of the most popular tools for altmetric analyses, PlumX and Altmetric.com, and we compare the results. Moreover, we study how open access and DOIs provided by Zenodo influence the impact of Zenodo data records and we find a tendency towards a positive relationship between permissive access rights and altmetrics in certain data records.